Aplikasi Nilai-Nilai Sufistik dalam Novel Rembulan Tenggelam di Wajahmu - Mulyani, Dewi Sri (Jurnal Riset Agama, 2023)
Literary works that have various purposes such as adding knowledge and entertaining make novels loved by the public in their spare time. Some novels written by the author have their own message to convey for readers. One of the values conveyed is sufistic values. The purpose of this study is to find this value in the novel under study and with it can be a means and implementation of sufistic studies on sufistic value analysis, can be a comparison of analyzing sufistic values in other novels and can be a contribution of thought for the general public in taking wisdom from each book read. This research is a literature study using a qualitative approach. The result and discussion of this study is that al-Ghazali's view of sufistic values is expressed as the meaning of sufism teachings that produce morality with connected science and charity. The sufistic value consists of maqamat as the sufi path includes taubat, sabar, faqir, zuhud, tawakal, mahabbah, ma’rifat and ridha. In this novel, sufistic values are also found according to al-Ghazali's views which include the eight points of maqamat which are listed in the narrative of the depiction of the story and the dialogue of the characters. Because this research uses one view of a Sufi figure, it is hoped that the next research can be a comparison by using the views of other Sufi figures.